1991
DOI: 10.1038/bjc.1991.206
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of carboplatin induced emesis by ondansetron

Abstract: al., 1988;Hesketh et al., 1989;Einhorn et al., 1990). In randomised studies it has been proven superior to both placebo (Cubeddu et al., 1990) and high dose metoclopramide (Marty et al., 1990) in controlling cisplatin induced emesis. In non-cisplatin containing chemotherapy regimens it has been shown superior to metoclopramide in four randomised studies (Schmoll, 1989;Kaasa et al., 1990).Vomiting after most chemotherapeutic agents tends to start within a couple of hours of treatment. The onset of vomiting afte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
1
1

Year Published

1993
1993
2002
2002

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 9 publications
0
7
1
1
Order By: Relevance
“…However, the results of this study show better efficacy than previously reported by Smith et al [6] and Harvey et al [7] where less than optimal doses of ondansetron com binations were administered. Similar results have, how ever, been observed in other studies where patients re ceived other non-cisplatin-based chemotherapy regimens.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…However, the results of this study show better efficacy than previously reported by Smith et al [6] and Harvey et al [7] where less than optimal doses of ondansetron com binations were administered. Similar results have, how ever, been observed in other studies where patients re ceived other non-cisplatin-based chemotherapy regimens.…”
Section: Discussioncontrasting
confidence: 56%
“…Two small studies have also been reported, one conducted in the United Kingdom and one in New Zea land [6,7], which suggest that although good response rates were observed during the acute phase of treatment, some 40-50% of patients experienced prolonged symp toms of emesis over the 4 days following carboplatin che motherapy.…”
Section: Introductionmentioning
confidence: 99%
“…Most of the patients suffered from severe emesis with a mean number of 13.5 vomiting episodes per patient. Data from 79 patients included in 3 anti-emetic trials using ondanse tron for the prevention of carboplatin-induced emesis were identified in a Medline literature search [11][12][13]. Although the numbers are small, there is clear evidence that ondansetron is efficacious in reducing carboplatin-induced emesis.…”
Section: Severity and Pattern Of Carboplatin-induced Em Esismentioning
confidence: 99%
“…The publications of these stud ies of 'noncisplatin-induced emesis' do not provide enough detailed data for a subgroup analysis of carboplatin-treated patients. A Medline search revealed only 3 studies of anti-emetic treatment for patients receiving car boplatin [11][12][13] . 3).…”
Section: Introductionmentioning
confidence: 99%
“…GR 38032F (ondansetron) is a selective serotonin sub type-3 receptor antagonist (5-HT;0, which has been pro posed to be effective in the prevention of nausea and vom iting associated with cisplatin and other chemotherapeu tic agents [1][2][3][4][5][6][7][8][9]. It is considered to be a major advance in the control of chemotherapy-induced emesis which is most severe and distressing in cisplatin-treated patients [10][11][12][13][14][15] but may also occur with other chemotherapy regi mens as well as radiotherapy and is paramount in the evaluation of patients for treatment of cancer [10][11][12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%